DEVELOPMENT OF A TRACTOR-MOUNTED DATE PALM TREE SERVICE MACHINE - Fadel, Moustafa A. (Emirates Journal of Food and Agriculture, 2017)
A tractor-mounted date palm tree service machine was developed and tested. The developed system is attached to the rear of an 80- HP agricultural tractor. System's power source is the tractor hydraulic system, electrically controlled using the tractor's electric DC circuit. Using the traditional tractor increases its annual working hours and reduce capital cost. The machine has the capability to lift a service worker and the required tools to the crown zone as high as 4.5 meters. A hydraulically driven winch is available to lower the harvested dates in a clean basket to the ground. To protect the worker from any system failures, and the tree from operator mistakes, both human and tree safety features are considered in the design. Compared to the traditional way of serving palm trees, where a worker climbs the tree using a piece of rope, the system provides a safer and more comfortable working environment. The developed system was tested in the field and compared with manual traditional practices. It was found out that using the developed device increases worker's productivity.